2022
DOI: 10.1038/s41467-022-29219-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein-based SARS-CoV-2 spike vaccine booster increases cross-neutralization against SARS-CoV-2 variants of concern in non-human primates

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants that partly evade neutralizing antibodies raises concerns of reduced vaccine effectiveness and increased infection. We previously demonstrated that the SARS-CoV-2 spike protein vaccine adjuvanted with AS03 (CoV2 preS dTM-AS03) elicits robust neutralizing antibody responses in naïve subjects. Here we show that, in macaques primed with mRNA or protein-based subunit vaccine candidates, one booster dose of CoV2 preS dTM-AS03 (mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 31 publications
1
45
2
Order By: Relevance
“…Our data are in line with a previous study in mice showing lower induction of nAbs (parental, Alpha, Beta and Gamma) with heterologous vaccination with S-trimer vaccine (D614 on D0 and Beta on D21), compared to 2-doses with a bivalent vaccine 40 . The limited breadth of responses observed with the 2-doses heterologous regimen contrasts with the expanded breadth of neutralizing responses observed recently after a late booster vaccine in NHPs and humans 14,15 . This likely relates to the absence of maturation of the memory B cell population when the second injection is performed shortly after the priming immunization (3 weeks here compared to 6 months to one year in the context of a booster vaccination) 41,42 .…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Our data are in line with a previous study in mice showing lower induction of nAbs (parental, Alpha, Beta and Gamma) with heterologous vaccination with S-trimer vaccine (D614 on D0 and Beta on D21), compared to 2-doses with a bivalent vaccine 40 . The limited breadth of responses observed with the 2-doses heterologous regimen contrasts with the expanded breadth of neutralizing responses observed recently after a late booster vaccine in NHPs and humans 14,15 . This likely relates to the absence of maturation of the memory B cell population when the second injection is performed shortly after the priming immunization (3 weeks here compared to 6 months to one year in the context of a booster vaccination) 41,42 .…”
Section: Discussioncontrasting
confidence: 63%
“…We recently showed that soluble prefusion-stabilized Spike trimers (CoV2 preS dTM) based on the D614 sequence formulated with the AS03 adjuvant elicited a favorable safety pro le and high immunogenicity against the parental strain in naïve adults 13 . In addition, we demonstrated that, in primed macaques, one booster dose of CoV2 preS dTM-AS03 (D614 or Beta) enhanced neutralizing antibodies against the parental virus and extended the neutralization to multiple VOC (Alpha, Beta, Gamma, Delta and Omicron) and SARS-CoV-1 14 . Preliminary data from two clinical trials assessing CoV2 preS dTM-AS03 as a booster in COVID-19 vaccine primed individuals con rmed these results and further suggested the superiority of the Beta monovalent vaccine formulations compared to D614 monovalent mRNA or subunit vaccines 15,16 .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, the platform is suitable for the developing world, because it is much cheaper and more stable than for example mRNA vaccines. We only recently started to gain more widespread clinical experience with this COVID-19 vaccine platform, for example the approved subunit vaccine Nuvaxovid ® from Novavax (Rockville, MA, United States) containing recombinant S protein formulated with the Matrix-M TM adjuvant (Heath et al, 2021), and clinical data are currently emerging for the COVID-19 vaccine from Sanofi-GlaxoSmithKline, which includes recombinant S protein formulated with the squalene oil-based adjuvant AS03 (Pavot et al, 2022).…”
mentioning
confidence: 99%